Attention deficit hyperactivity disorder (Portuguese Journal of Family Medicine and General Practice, 2004)
Attention-deficit hyperactivity disorder (ADHD) is the most common neuro-behavioural disorder in children. It persists through the teens to adult age, with unclear prevalence rates in those age groups. Every child between 6 and 12, presenting with attention deficit, impulsiveness, hyperactivity, poor school results or behavioural problems, should be screened for ADHD. The high prevalence of this problem in the school population underscores the need for the family doctor, along with the pediatrician, to be proficient in its early identification and assessment. ADHD calls for a multidisciplinary approach, with active involvement of the family, teachers, psychologists and, occasionally, pedopsychiatrists and neuropediatricians, along with the family doctor or pediatrician. The main objective of the treatment is the maximization of the child function and performance at home, school and community, reducing disruptive behaviour and enhancing school performance, independence and self-esteem.
Keywords: Attention; Hyperactivity; Impulsiveness; Attention-Deficit Hyperactivity Disorder; ADHD